Stabilization of an epidemic model via an N-periodic approach - Cantó, Begona; Coll, Carmen; Sánchez, Elena (Zielona Góra: Uniwersytet Zielonogórski)
We analyze the evolution of an infectious disease by combining different groups of a population when the route of transmission is via encounters with free-living virulent organisms that can survive for a long time outside the individual. This study involves matrix analysis of lower triangular block matrices and some of their spectral properties. We propose an N-periodic control strategy in order to stabilize the disease around the disease-free equilibrium point.
Keywords: nonnegative matrix; stability; reducible matrix; seasonality; epidemic process